THE ROLE OF INDONESIAN GOVERNMENT DIPLOMACY AND INTERNATIONAL LAW IN BUSINESS PROVIDING PROTECTION FOR INDONESIAN MIGRANT WORKERS - Felix Ferdin Bakker; Muhammad Brian Dananjaya (Journal of Law and Border Protection, 2022)
With a population that is above average, Indonesia has a high number of migrant workers residing abroad. This happens because of the impact of globalization and is also one of Indonesia's ways to reduce unemployment in the country. It is undeniable that from this, there will be problems and obstacles that approach. The problem of migrant workers who are abroad is currently a special concern of the Indonesian government as a guarantee that the state's goal to protect the entire nation is carried out. By using descriptive research methods obtained from various sources listed, the authors get the data that will be presented in this paper. This writing also uses a normative juridical approach. Protection in the form of a legal umbrella from Indonesia and Indonesian legal entities abroad is an important factor as a support for protecting migrant workers. With a focus on international and national law, Indonesia tries its best to carry out this protection optimally.